PENGARUH BUDAYA ORGANISASI, PENGALAMAN, OTONOMI, PROFESIONALISME DAN AMBIGUITAS PERAN TERHADAP KINERJA AUDITOR (Studi Empiris Pada KAP di Jawa Tengah) - Indah Dwi Ratnasari, 13.05.52.0053; Badjuri, Achmad (Students Journal of Accounting and Banking, 2017)
This study aimed to examine the effect of Organizational culture, experience of auditor, autonomy, profecionalism, and role ambiguity of audit performance The population in this study were all auditors working in the public accounting firm in Central Java. Sampling was done using purposive sampling method and sample size were 65 respondents. The primary data collection method used survei method was used a questionnaire . Data were analyzed using multiple linier regression model.Â Result of research indicate that the variables Organizational culture, experience of auditor, autonomy, and profecionalism have significant positive effect to audit performance, while role ambiguity variable has significant negative effect to auditor performance.Keywords: Organizational Culture, Experience of Auditor, Autonomy, Profecionalism, Role Ambiguity and Auditor Performance